2012
DOI: 10.1007/s00330-012-2583-2
|View full text |Cite
|
Sign up to set email alerts
|

Separation of advanced from mild hepatic fibrosis by quantification of the hepatobiliary uptake of Gd-EOB-DTPA

Abstract: Liver fibrosis stage strongly influences the hepatocyte-specific uptake of Gd-EOB-DTPA. Potentially the normalisation technique and K (Hep) will reduce patient and system bias, yielding a robust approach to non-invasive liver function determination.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
53
1

Year Published

2013
2013
2017
2017

Publication Types

Select...
9
1

Relationship

2
8

Authors

Journals

citations
Cited by 65 publications
(57 citation statements)
references
References 29 publications
3
53
1
Order By: Relevance
“…In previous studies with Gd-EOB-DTPA in clinic, the evaluation of liver fibrosis focus on the slope, the contrast agent uptake rate ( K Hep ), liver-to-spleen contrast ratios (LSC) and RE and so on [9, 3233]. Chen BB [9] found slope and AUC were the best perfusion parameters to predict the severity of liver fibrosis in their study.…”
Section: Discussionmentioning
confidence: 99%
“…In previous studies with Gd-EOB-DTPA in clinic, the evaluation of liver fibrosis focus on the slope, the contrast agent uptake rate ( K Hep ), liver-to-spleen contrast ratios (LSC) and RE and so on [9, 3233]. Chen BB [9] found slope and AUC were the best perfusion parameters to predict the severity of liver fibrosis in their study.…”
Section: Discussionmentioning
confidence: 99%
“…Regarding contrast-enhanced MR, especially with gadolinium-EOB-DTPA, a reduced SI in patients with cirrhosis is mostly reported. Particularly, Feier et al [81] found that relative enhancement values correlated strongly with fibrosis stage, with an AUC of 0.83 for > F4; Norén et al [82] found that liver-to-spleen contrast ratios at 10 and at 20 min and contrast uptake rate had AUROCs values of respectively 0.80, 0.78, and 0.71 with regard to severe vs mild fibrosis; Verloh et al [83] found that the mean relative enhancement in patients with Child-Pugh Score A cirrhosis had significant increase between arterial, late arterial, portal and hepato-biliary phases, while for Child-Pugh B+C cirrhosis, relative enhancement increased until portal phase and was significantly reduced in C cirrhosis during hepatobiliary phase; Nojiri et al [84] found that SI at 25 min could discriminate F = 0-3 vs F = 4, with AU-ROC of 0.87; Goshima et al [85] reported that sensitivity, specificity, and AUROC demonstrated by linear regression formula generated by volumetric ratio and contrast enhancement index in predicting fibrous scores were 91%, 100% and 97% for F4. Kim et al [86] reported that the relative enhancement [(hepatocyte phase SI -precontrast SI)/pre-contrast SI] of patients with Child-Pugh cirrhosis was significantly higher than that of patients with Child-Pugh B or C cirrhosis.…”
Section: Mrmentioning
confidence: 98%
“…In cirrhosis, hepatocytes are progressively replaced by fibrotic tissue, so that the more advanced the fibrosis, the smaller the hepatic parenchyma enhancement in the hepatobiliary phase. Additionally, as compared with healthy livers, cirrhotic livers present later enhancement peak and slower washout (32-37) . Further potential hepatobiliary contrast applications include the evaluation of the functional hepatic reserve before partial hepatectomy; evaluation of live donor's hepatic function as well as evaluation of early liver failure after transplant (4) .…”
Section: Assessment Of Hepatic Fibrosismentioning
confidence: 99%